A Spatial Study of X-ray Properties in Superbubble 30 Dor C with XMM-Newton. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Babazaki, Y.; Mitsuishi, I.; Sano, H.; Yoshiike, S.; Fukuda, T.; Maruyama, S.; Fujii, K.; Fukui, Y.; Tawara, Y.; Matsumoto, H
Abstract: The superbubble (SB) 30 Dor C with the strong non-thermal X-ray emission is one of the best targets for study of the cosmic-ray (CR) acceleration. We investigated X-ray spectral properties of the SB with a high spatial resolution of ~10 pc. Consequently, the spectra in the east regions can be described with a combination of absorbed thermal and non-thermal models while the spectra in the west regions can be fitted with an absorbed non-thermal model. We found that the observed photon index and intensity in 2-10 keV show variations of 2.0-3.5 and (0.6-8.0) × 10 −7 erg s −1 cm −2 str −1, respectively. The results are possibly caused by the spatial variation of the CR acceleration efficiency and/or the circumstellar environment.